ANALISIS SIFAT MEKANIK DAN KARAKTERISTIK BATU BATA MERAH DENGAN MENGUNAKAN METODE RSM DI KABUPATEN BANGKA - Ludy Firmansyah; Yuliyanto Yuliyanto; Nanda Pranandita (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Red bricks are the most easy material to locate and use practically any building. Besides being cheap, red bricks are also often used because of their easy and plentiful production processes in all parts of Indonesia. Brick use in both construction and non-construction or structure needs to be increased products produced, either by improving the quality of the red brick matality or additions to other materials.. Based on sni 15-2094-2000, red bricks are a rectangular prism material, solid or perforated with a hole volume ata maximum of hole volume at 15% and are used for constructing walls of buildings, which are made of clay with or without active material and burned ata certain temperature. The study was done using the RSM method of using soft prelims. The data processing produced 20 samples with six times the repetition in the center. The results of this study were the result of the highest impaction in experiments 14, 122.9 kj/m2, with a 8-day drying parameters, a temperature of 968.18oc with a 10-hour heat span and the lowest impact on experiment 12 was 47.6 k Kj /m2 with the long drying parameters of 8 days, places up to 800oc and a length of warming 3.27 hours this is due to the long drying and long warming. Based on shem's test, the exact difference in the form of breaking the value of the broken impak tests shows that the surface has become crystalline with perfect uniform. even though some of the parts are cracked, it is because the water contained less than the lower intake, which forms the crystals at least 50%, while in some areas there is a portation or hole in which the convergence is still incomplete.